PKM Katekese Tentang Menghayati Nilai Kekeluargaan dalam Era Digital bagi Para Orangtua Peserta Komuni Pertama - Aurelius Fredimento; Gregorius Sebo Bito; Berty Sadipun; John M Balan; Nong Hoban (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
The communication media  as a work of human beings reason from time to time has a very rapidly progress together with the growth and the development of new innovations in the world of the digital technology. This progress is a  certainty that must be received by the human beings who are in a strong mind and conscience awareness that communication media is so sophisticated but remains as a means of the development of the human beings civilization. This awareness gradually can be expected to encourage human beings in order to place themselves appropriately as the subject of the  development of the communication media itself through a rational and an accurate filtering process against negative influences that can threaten with human beings civilization. One of the institutions is threatened with the negative  influences of the communicaton media is family. At first the family gets a respected  position as a socialization agent about the values of life is now experiencing decline of function as well as its role because the majority of the family members are now snared because of the negative influences of the communication  media. The sympathetic as well as the  empathetic atmosphere are used to be the first decoration in the  house and now  is just becoming a nice memory but sadden. The fascination  is too axtreme makes each of the family member of the communication media and finally appear some attitudes as well as behaviours that don,t go with the values of solidarity and the family as well. At last, this problem lets grow as well  as develop without striving for preventive and curative of the various social elements. This meant preparing a show of a destruction of the generation in the future. Therefore, the whole sides are expected to their involvement to be a foremost line in preventing efforts. On the basis, the Paroki St. Yosef Onekore is also moved at giving the basics  correct of comprehension to the parents in the catechetical activities  that the communication media is actually just a means of using it to proclaim the King of God.